2016
DOI: 10.1891/1945-8959.15.3.391
|View full text |Cite
|
Sign up to set email alerts
|

Training Problem Solving and Organizational Skills in Adolescents With Attention-Deficit/Hyperactivity Disorder: A Randomized Controlled Trial

Abstract: Attention-deficit/hyperactivity disorder (ADHD) is a highly prevalent psychiatric disorder in adolescence and results severe impairment. Few psychosocial interventions aim at ADHD in adolescence and are rarely evaluated in randomized controlled trials (RCTs). Therefore, an intervention combining adolescent-directed problem-solving and organizational skills training with behavioral parent and teacher training has been developed. Its efficacy in comparison to waiting list and active controls is reported.One hund… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 46 publications
0
10
0
2
Order By: Relevance
“…The most comprehensive review to date aimed to identify randomized controlled trials (RCTs) including both children and adolescents, but found no RCTs for adolescents in its original review (Storebø et al, 2011). Recently updated (Storebø et al, 2019), subgroup analyses included one RCT for adolescents (defined as 12-18 years) which utilized a more general cognitive-behavioral curriculum of problem-solving and organizational skills, rather than an explicit focus on SST (Schramm et al, 2016). The review concluded that there was not enough quality evidence to support or refute the efficacy of social skills interventions for children and adolescents with ADHD (Storebø et al, 2019).…”
Section: Interventions To Improve Social Functioning In Youth Withmentioning
confidence: 99%
“…The most comprehensive review to date aimed to identify randomized controlled trials (RCTs) including both children and adolescents, but found no RCTs for adolescents in its original review (Storebø et al, 2011). Recently updated (Storebø et al, 2019), subgroup analyses included one RCT for adolescents (defined as 12-18 years) which utilized a more general cognitive-behavioral curriculum of problem-solving and organizational skills, rather than an explicit focus on SST (Schramm et al, 2016). The review concluded that there was not enough quality evidence to support or refute the efficacy of social skills interventions for children and adolescents with ADHD (Storebø et al, 2019).…”
Section: Interventions To Improve Social Functioning In Youth Withmentioning
confidence: 99%
“…However, such changes in perceptions may of course be important psychological indicators of the rater's beliefs about child behavior (even if not accompanied by actual changes in core symptoms). It could also be argued that intervention recipients themselves (parents or teachers in the instance of children) are the best raters of the child's problems 44 . Further, parent and teacher reported outcomes are better translatable to clinicbased practices, as they are nearly always the only available information source in clinical care.…”
Section: Discussionmentioning
confidence: 99%
“…Our literature search on psychosocial interventions yielded 13 trials, with 1812 participants (range 46-326) fulfilling our selection criteria (Table 3). Five studies examined psychosocial interventions provided to students with ADHD in a school setting [62][63][64][65][66] and eight studies tested psychosocial interventions in a clinical setting [67][68][69][70][71][72][73][74]. The studies included family-focused parenting interventions or adolescent-focused cognitive behavioral and/or MI-based interventions either with or without a parent component.…”
Section: Adolescents With Adhd But Without Sud Comorbiditymentioning
confidence: 99%